2010
DOI: 10.1007/s00039-010-0058-7
|View full text |Cite
|
Sign up to set email alerts
|

Ergodic Subequivalence Relations Induced by a Bernoulli Action

Abstract: Let Γ be a countable group and denote by S the equivalence relation induced by the Bernoulli action Γ [0, 1] Γ , where [0, 1] Γ is endowed with the product Lebesgue measure. We prove that, for any subequivalence relation R of S, there exists a partition {X i } i≥0 of [0, 1] Γ into R-invariant measurable sets such that R |X0 is hyperfinite and R |Xi is strongly ergodic (hence ergodic and non-hyperfinite), for every i ≥ 1.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 25 publications
6
69
0
Order By: Relevance
“…The proof of [8], Lemma 5 provides a family {A i } i∈I of von Neumann subalgebras of M 1 and a family {Γ i } i∈I of finite subgroups of Γ 1 such that…”
Section: Proof Of Theorem 32 Assuming Thatmentioning
confidence: 99%
“…The proof of [8], Lemma 5 provides a family {A i } i∈I of von Neumann subalgebras of M 1 and a family {Γ i } i∈I of finite subgroups of Γ 1 such that…”
Section: Proof Of Theorem 32 Assuming Thatmentioning
confidence: 99%
“…Now, the desired result is an immediate consequence of (2) and [3,Theorem 1.3] from the work of Epstein-Monod.…”
Section: B(h)mentioning
confidence: 86%
“…It is not known whether rigidity implies strong ergodicity for equivalence relations (this question has been communicated to me by S. Popa). An affirmative answer to this question together with Theorem 3.1 would provide a different proof of N. Ozawa's result saying that any ergodic, nonhyperfinite subequivalence relation R of S is strongly ergodic (see [37] and [6]). …”
Section: Remarks (A)mentioning
confidence: 92%
“…Thus, it is proven in [43, 5.2], that, if S is the equivalence relation induced by a Bernoulli action of a countable group, then the II 1 factor L(R) is prime, for any ergodic, non-hyperfinite subequivalence relation R of S. Moreover, as shown in [6], any such R is strongly ergodic (see [36] in the case of exact groups Γ ). Recently, N. Ozawa has shown that, in the context of 0.1, any ergodic subequivalence relation R is either hyperfinite or strongly ergodic [37].…”
Section: Introductionmentioning
confidence: 90%